2006
DOI: 10.1620/tjem.210.341
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Decrease in Bone Mineral Density in Women Aged 52-57 Years

Abstract: Bone mineral density (BMD) has been known to decline in middle-aged and elderly individuals, but when this decline begins and the rate at which it occurs remain unclear. We thus undertook this study to examine the association between BMD and age by their mean values in women visiting the Shimane Institute of Health Science for medical examination. We performed dual energy X-ray absorptiometry measurement of lumbar vertebrae in 1,167 women, and of the entire skeleton in 1,038 women. The ages of subjects ranged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
(17 reference statements)
1
11
0
3
Order By: Relevance
“…However, RTBA of the calcaneus was higher in girls than in boys. We consider this to be related to the female hormone (Nohara et al 2006); however, we did not investigate the relationship with sex characteristics such as menarche in girls, as we thought that objective data would be difficult to be obtained. One study found that age at onset of puberty, peak height velocity, and menarche was about 9.5, 11, and 12 years, respectively in Japanese girls (Tanaka and Imai 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, RTBA of the calcaneus was higher in girls than in boys. We consider this to be related to the female hormone (Nohara et al 2006); however, we did not investigate the relationship with sex characteristics such as menarche in girls, as we thought that objective data would be difficult to be obtained. One study found that age at onset of puberty, peak height velocity, and menarche was about 9.5, 11, and 12 years, respectively in Japanese girls (Tanaka and Imai 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Soon after menopause the osteoporotic risk for women increases. This is due to accelerated bone remodeling as a consequence of estrogen withdrawal 3 . Therefore, it is important to identify postmenopausal women at high risk for future fractures in order to develop effective preventive treatment.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to accelerated bone remodeling as a consequence of estrogen withdrawal. 3 Therefore, it is important to identify postmenopausal women at high risk for future fractures in order to develop effective preventive treatment. In this context, measurement of bone mineral density (BMD) is of considerable clinical relevance because BMD is one of the best predictors of future osteoporotic bone fractures.…”
Section: Introductionmentioning
confidence: 99%
“…BMD is the most frequently used measurement for diagnosing osteoporosis and monitoring osteoporosis treatments in postmenopausal women (Nohara et al 2006). However, changes in BMD following osteoporosis treatment only appear after 6 months or longer.…”
Section: Discussionmentioning
confidence: 99%